THE ROLE OF USING STRATEGIC PROFITABILITY ANALYSIS IN MAXIMIZING SHAREHOLDERS VALUE IN ECONOMIC UNITS: AN APPLIED STUDY IN DAIRY FACTORY (GULE LADE) - Assist. prof. Dr. Hazim Hashim Mohammed (PalArch's Journal of Archaeology of Egypt / Egyptology, 2021)
In the light of globalization and the new changes, challenges are becoming bigger, competition is intensifying and enterprises find themselves looking for appropriate solutions to keep pace with changes in the field of science and technology and to maintain their market shares that ensure their survival, and maximize their profits to develop their competitiveness. The clear vision of the future provides sufficient flexibility and the ability to respond to various and fast changes which imposed by the competitive environment. The researcher relied on dairy factory "Gule Lade" data for 2018, 2019, to show the use of strategic profitability analysis and their role on shareholder value metrics to improve the performance of the factory and to achieve the best quality of products at competitive prices that maximizes profits and develops their competitiveness compared to its competitors. The researcher used the practical approach to achieve the objectives of the study and test its hypotheses through the use of strategic profitability components to maximize shareholder value through its selected measures based on the actual data of the "dairy factory Gule Lade" To produce yogurt, cheese and qaimer It is the applied aspect of the study. One of the most important results of the study that the researcher has reached is that there is a relationship between the components of strategic profitability and shareholder value through their measures and the impact between them. The study concluded with several recommendations, the most important of that is the need of industrial companies to pay attention to the local environment in using the technique of strategic profitability analysis for the purposes of cost leadership, product differentiation and growth to keep pace with the changes taking place in the competitive environment, in order to maximize the value of shareholders.